1994
DOI: 10.1042/bj3030121
|View full text |Cite
|
Sign up to set email alerts
|

Major proteins of bovine seminal plasma inhibit phospholipase A2

Abstract: We have recently shown that the major proteins of bovine seminal plasma, namely BSP-A1, BSP-A2, BSP-A3 and BSP-30-kDa (collectively called BSP proteins) bind to spermatozoa and that the binding sites on the plasma membrane of spermatozoa are choline phospholipids. In view of the fact that these phospholipids are substrates for phospholipase A2 (PLA2), a key enzyme in sperm capacitation and the acrosome reaction, the effect of BSP proteins on this enzyme activity was investigated. Since these BSP proteins are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…High levels of secretory phospholipase A 2 have indeed been observed in seminal plasma samples of healthy donors as a product of the prostate (39). On the other hand, seminal plasma also contains potent phospholipase A 2 protein inhibitors (40,41), and it is not known whether the enzyme is active in ejaculates.…”
Section: Discussionmentioning
confidence: 98%
“…High levels of secretory phospholipase A 2 have indeed been observed in seminal plasma samples of healthy donors as a product of the prostate (39). On the other hand, seminal plasma also contains potent phospholipase A 2 protein inhibitors (40,41), and it is not known whether the enzyme is active in ejaculates.…”
Section: Discussionmentioning
confidence: 98%
“…The PDC-109 protein reduces membrane fluidity and immobilises cholesterol in phospholipid membranes, including those of epididymal spermatozoa (Greube et al 2001;Müller et al 2002). In addition, PDC-109 can contribute to membrane stability by inhibiting the activity of phospholipase A 2 (Manjunath et al 1994;Soubreyrand and Manjunath 1997). Thus, PDC-109 may play a role in preserving bull sperm fertility while spermatozoa are stored in the reservoir.…”
Section: Preserving Sperm Fertility During Storagementioning
confidence: 99%
“…1). Manjunath et al (1994) reported the purification and biochemical characterization of four GB-proteins and designated them as BSP-A1, BSP-A2, BSP-A3 and BSP-30-kDa. BSP-A1/-A2 or PDC-109 was named following the Ion-E x Chr.…”
Section: Isolation and Purification Of Pdc-109 Proteinmentioning
confidence: 99%